1990
DOI: 10.1177/000348949009900612
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance and Chronic Secretory Otitis Media in Children: Effect of Myringotomy and Insertion of Ventilation Tubes on Body Sway

Abstract: We studied balance in 34 children with chronic secretory otitis media and compared them with 34 age- and sex-matched control children between the ages of 3 and 5 years. In addition to history and examination, objective measurements were obtained by use of a fixed force plate body sway platform in both the control group and the group with chronic secretory otitis media. We took measurements in both groups at an interval of 4 months to ensure that any improvement in body sway could not be attributed to normal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 14 publications
(6 reference statements)
2
25
0
Order By: Relevance
“…The epidemiological finding of clumsy behaviour associated with middle ear disease adds to clinical research,22 23 suggesting possible vestibular side effects of middle ear disease. The Dunedin study21 found deficits of motor skills from a history of middle ear disease.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological finding of clumsy behaviour associated with middle ear disease adds to clinical research,22 23 suggesting possible vestibular side effects of middle ear disease. The Dunedin study21 found deficits of motor skills from a history of middle ear disease.…”
Section: Discussionmentioning
confidence: 99%
“…This difference resolved four months following myringotomy with tube insertion. 12 Hart and colleagues (1998) compared 19 four- to six-year-old children with OME scheduled for tympanostomy tube insertion to 14 matched controls using the Peabody Developmental Motor Scales and the Bruininks-Oseretsky Test of Motor Proficiency, two validated testing instruments of motor and balance development. The OME group demonstrated significantly lower performance in the balance subscales prior to tube insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al [18] found much worse stabilogram parameters in 34 children with OME in comparison to the control group. Certain disturbances in posturographic tests performed on children with OME were also observed by Casselbrant et al [2], who maintain that those disturbances may impair the child's motor development.…”
Section: Discussionmentioning
confidence: 93%